2024
DOI: 10.1161/circulationaha.123.065517
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Communication by SGLT2 Inhibition

Anja M. Billing,
Young Chul Kim,
Søren Gullaksen
et al.

Abstract: BACKGROUND: SGLT2 (sodium-glucose cotransporter 2) inhibitors (SGLT2i) can protect the kidneys and heart, but the underlying mechanism remains poorly understood. METHODS: To gain insights on primary effects of SGLT2i that are not confounded by pathophysiologic processes or are secondary to improvement by SGLT2i, we performed an in-depth proteomics, phosphoproteomics, and metabolomics analysis by integrating signatures from multiple metabolic organs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Canagliflozin, a SGLT2 inhibitor, optimized gut microbiota composition via increased cecal short-chain fatty acids, reduced serum IS levels, and suppressed systemic inflammation and kidney injury [ 120 ]. SGLT2 inhibitors have also been shown to alter the gut microbiota and potentially reduce the production of uremic toxins derived from amino acids, as revealed in proteomics analyses using mice [ 121 ].…”
Section: Therapeutic Strategies For Atherosclerosis Caused By Spbmsmentioning
confidence: 99%
“…Canagliflozin, a SGLT2 inhibitor, optimized gut microbiota composition via increased cecal short-chain fatty acids, reduced serum IS levels, and suppressed systemic inflammation and kidney injury [ 120 ]. SGLT2 inhibitors have also been shown to alter the gut microbiota and potentially reduce the production of uremic toxins derived from amino acids, as revealed in proteomics analyses using mice [ 121 ].…”
Section: Therapeutic Strategies For Atherosclerosis Caused By Spbmsmentioning
confidence: 99%
“… 3 , 4 More than 80% of patients with AF suffer from comorbidities, such as hypertension, heart failure, diabetes, or coronary, cerebral, or peripheral artery disease at the time of diagnosing AF. 4 , 5 These include cardiometabolic dysfunction, 6 systemic and atrial thromboinflammation, 7 , 8 vascular and endothelial dysfunction, 7 , 8 and cardiomyocyte dysfunction. 9 Quantification of underlying disease processes and their interactions may identify drivers of cardiovascular complications in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…Empagliflozin also ameliorated anthracycline-associated cardiotoxicity [ 15 ] leading to the multicenter phase 3 study EMPACT (NCT05271162). Finally, a recent unbiased proteomics and metabolomics study showed that SGLT2i mainly affect the gut microbiome and the kidney, where they induce less production and greater excretion of amino acid metabolites (“uremic toxins”) with cardiodepressant effects [ 2 ].…”
mentioning
confidence: 99%